Kinetics, Stereospecificity, and Expression of the Malolactic Enzyme - Arthurs, Ceri E. (American Society for Microbiology, 1999)
Mass spectrometric measurement of carbon dioxide production was used to study malolactic fermentation (MLF) in Lactobacillus collinoides isolated from cider. The kinetics and stereospecificity of the malolactic enzyme (MLE) were studied, and the stoichiometry of the reaction sequence was investigated. The optimum pH for activity of the MLE was 4.9. MLF was more rapid (in both intact cells and cell extracts) when l-malic acid was used than when d-malic acid or the racemic mixture was added. The enzyme was found to be constitutively present in L. collinoides. Addition of l-malic acid (37 mM) to the growth medium resulted in increased MLE activity; addition of the d isomer alone or the racemic mixture resulted in lower activities. Addition of the main sugars in apple juice (fructose, sucrose, and glucose) to the growth medium in the presence of malic acid repressed production of MLE to similar extents in all three cases; in the absence of malic acid, instead of inhibiting MLF, addition of sugars to the growth medium somewhat increased the residual MLE activity.